2012
DOI: 10.1039/c2mt20021j
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between copper and cisplatin transport mediated by human copper transporter 1 (hCTR1)

Abstract: Copper transporter 1 (CTR1) is a transmembrane protein that imports copper(i) into yeast and mammalian cells. Surprisingly, the protein also mediates the uptake of platinum anticancer drugs, e.g. cisplatin and carboplatin. To study the effects of several metal-binding residues/motifs of hCTR1 on the transport of both Cu(+) and cisplatin, we have constructed Hela cells that stably express a series of hCTR1 variant proteins including H22-24A, NHA, C189S, hCTR1ΔC, H139R and Y156A, and compared their abilities to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“… 11 HeLa cells overexpressing CTR1 show 2.2-fold increase in cisplatin accumulation compared with the mock-transfected cells. 12 Du et al 12 found that the C-terminus of CTR1 protein was required for cisplatin uptake in HeLa cells. In a mouse model of cervical cancer, Ishida et al 13 demonstrated that the level of DNA–cisplatin adducts correlated with CTR1 mRNA level in various organs, suggesting that CTR1 may regulate cisplatin uptake in vivo.…”
Section: Mechanisms Underlying Cprmentioning
confidence: 99%
“… 11 HeLa cells overexpressing CTR1 show 2.2-fold increase in cisplatin accumulation compared with the mock-transfected cells. 12 Du et al 12 found that the C-terminus of CTR1 protein was required for cisplatin uptake in HeLa cells. In a mouse model of cervical cancer, Ishida et al 13 demonstrated that the level of DNA–cisplatin adducts correlated with CTR1 mRNA level in various organs, suggesting that CTR1 may regulate cisplatin uptake in vivo.…”
Section: Mechanisms Underlying Cprmentioning
confidence: 99%
“…Mutations to Ala of residues at the entrance of the copper translocation pathway (Met150 and Met154 in the TM2) eliminate copper uptake. In contrast, mutations/deletions of Met, His, or Cys residues in the N-terminal or C-terminal tails of hCTR1, respectively, change the rate of transport (Du, Wang, Li, & Sun, 2012), but do not fully abolish the transport activity, pointing to the regulatory functions for the N-terminal and C-terminal copper-binding sites. The binding of copper to one or more of such regulatory sites and subsequent conformational changes in the protein (Eisses & Kaplan, 2002) are likely to be the first steps toward hCTR1 internalization.…”
Section: Copper Auto Regulates Its Cytoplasmic Levels By Modulating Tmentioning
confidence: 99%
“…The proteins involved in this regulatory system share cysteine-based motifs—a common motif is CXXC (where X can be any amino acid), which has a high affinity for Cu(I) binding, allowing concurrently its rapid release to the next CXXC-containing protein target along the copper transport route [4,5]. Resolving the copper cycle in eukaryotic and prokaryotic systems is of utmost importance for several reasons: (1) Disruption of copper homeostasis has been shown to lead to various neurological diseases (such as Alzheimer’s, Parkinson’s, and Prion’s disease) [6,7]; (2) the copper cycle is used in the shuttling of metal-based therapeutic drugs such as cisplatin chemotropic compound [8,9,10,11]; (3) copper has been used for thousands of years as an antibacterial agent [12,13]. Hence, gaining an in-depth understanding of how these systems work, both in eukaryotic and prokaryotic cells, can assist in devising innovative strategies to control the in-cell Cu(I) concentration according to health needs, either by developing novel drug candidates or by designing a new generation of antibiotics.…”
Section: Introductionmentioning
confidence: 99%